Incidence of antibiotic-associated diarrhea in a pediatric ambulatory care setting - Alisara Damrongmanee (2018)
Background: Although antibiotic-associated diarrhea (AAD) is a common adverse event in children receiving oral antibiotics, few epidemiological studies have investigated this issue. Objective: To determine the incidence of AAD in children who received oral antibiotics at the Pediatric Outpatient Department, Chiang Mai University Hospital. Material and Method: Children who were prescribed oral antibiotics between September 2004 and June 2005 were randomly enrolled. Subjects with immunodeficiencies, acute/chronic diarrhea, and a history of having taken antibiotics within two weeks prior to this visit were excluded. Patients' characteristics including age, gender, principal diagnosis, and type of antibiotics were recorded. Parents were asked to observe stool frequency and consistency until one week after discontinuing antimicrobial agents and fill out an appropriate questionnaire. AAD was defined if there were at least three loose or liquid stools per day for two consecutive days. Risk factors including age, type, and dosage of the antibiotics used, were analyzed. Results: Two hundred and twenty-five children were eligible for data analysis. The mean age was 4.1 years (0.3-14.5 years). Pharyngotonsillitis was the most common diagnosis (53.8%), and amoxicillin and cloxacillin comprised the most common antibiotics prescribed in the present cohort. The incidence of AAD was 6.2%. All episodes were presented while the patients were taking antibiotics with a mean (+/- SD) onset and duration of occurrence of 2.28 +/- 1.13 and 2.64 +/- 1.15 days, respectively. Premature discontinuation of antimicrobial agents was reported in nine patients (64.3%). There was a trend towards a higher incidence of AAD in the amoxicillin/clavulanate group (16.7%) compared to amoxicillin (6.9%) and erythromycin (11.1%) groups, although it was not statistically significant. In addition, the present study could not demonstrate an association between younger age or the high dosage of antibiotics used, and the development of AAD. Conclusion: AAD was not uncommon in a pediatric ambulatory care setting. It tended to occur in younger children receiving amoxicillin/clavulanate.